Evaluation Of Acoustic Emission Behavior Under Hydrostatic Test In Api 5l X70 Steel Pipe - M.F, Yusoff (2010)

(untitled)
Acoustic emission is a very important test among non-destructive tests, and it has been applied for the detection of failures in various types of equipment in the petroleum industry, such as pressure vessels, tanks and pipelines. This paper presents the investigation of AE behaviour during tensile deformation and hydrostatic test of API 5L X70 steel which was widely used as oil and gas pipe material. Results indicated that AE phenomena was very active during elastic region. Detail analysis been done in elastic region, it was found that AE amplitude and energy gave small value during initial portion of elastic region and reach the peak value in the second stage just before yielding occurs. Load tensile test and pressurize in pipe were performed and measurements were made over the entire stress range in order to determine the stress- dependence of acoustic activity.